Law Enforcement Against Perpetrators of Fraud Crime Under the Guise of Online Social Gathering - Fernando, Youngky (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2022)
This research aims to determine law enforcement against perpetrators of online social gathering fraud crimes. Method The empirical juridical approach is legal science research that examines law as a fact that can be consolidated or observed and is value-free and has characteristics, namely, distinguishing facts from norms, legal phenomena must be purely empirical, namely social facts. Field observation data collection method to observe scientifically, empirically and value-free. Direct interviews with respondents directly. Literacy study of archives and records of siding results. The results of research on Jambi Regional Police's law enforcement efforts regarding cases of fraud under the guise of online social gatherings in the Jambi City jurisdiction, namely that based on the role of Jambi City Resort Police legal officers, criminal acts of this type of fraud under the guise of online social gatherings can be prosecuted. Law enforcement efforts carried out by the police are carried out in two stages, namely the prevention stage and the action stage (refresive). The process of resolving criminal cases of fraud under the guise of online social gatherings at the Jambi Regional Police from 2018-2021 as many as two of the same cases can be resolved by the Jambi Regional Police, which is carried out in four stages, starting from the investigation stage, investigation stage, examination stage to the settlement stage and handing over the case to the Public Prosecutor (JPU)